(untitled) (Itinera, 2013)
There is a significant difference between Shakespeare’s plays and Verdi’s melodramas: the complex modern-bourgeois Weltanschauung of Verdi’s works, whose central personage is always dialectically engaged with other social figures and is characterized by the force of impetuous passion. Robert Wilson’s staging of Macbeth accurately interprets the sense of the grotesque that inspired Verdi, resonating with the particular blend (gestalt) of words, music and sets intended by the Maestro of Busseto and ably appropriated by the Texan director, who coherently presents the score and the theme of passion objectively, distancing it from the character who experiences pathos on stage, produced by an internal conflict of an ethicalsocial nature.